2010
DOI: 10.5194/acp-10-9451-2010
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model assessment of stratospheric ozone return dates and ozone recovery in CCMVal-2 models

Abstract: Projections of stratospheric ozone from a suite of chemistry-climate models (CCMs) have been analyzed. In addition to a reference simulation where anthropogenic halogenated ozone depleting substances (ODSs) and greenhouse gases (GHGs) vary with time, sensitivity simulations with either ODS or GHG concentrations fixed at 1960 levels were performed to disaggregate the drivers of projected ozone changes. These simulations were also used to assess the two distinct milestones of ozone returning to historical values… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
216
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 229 publications
(240 citation statements)
references
References 60 publications
20
216
4
Order By: Relevance
“…Newchurch et al 2003;Angell and Free 2009;Eyring et al 2010;Krzyścin 2010;Zhang et al 2014;Chipperfield et al 2017). However, some studies have shown that stratospheric ozone concentrations over different regions along the same latitude exhibit different recovery rates.…”
Section: Introductionmentioning
confidence: 99%
“…Newchurch et al 2003;Angell and Free 2009;Eyring et al 2010;Krzyścin 2010;Zhang et al 2014;Chipperfield et al 2017). However, some studies have shown that stratospheric ozone concentrations over different regions along the same latitude exhibit different recovery rates.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal evolution of the Ozone-Depleting Substances (ODSs) and GHGs mixing ratios were derived from observations for the 1961-2006 period, and then according to one ODS scenario and two different GHG scenarios from the CCMVal project for the 2007-2100 period: REF2 and SCN-B2c (Morgenstern et al 2010, Eyring et al 2010b. The evolution of ODSs in REF2 is based on the scenario A1 from WMO (2007), but slightly modified to account for the earlier phase out of HCFCs agreed upon at the 2007 Meeting of the Parties to the Montreal Protocol (Morgenstern et al 2010).…”
Section: Lmdz-reprobus Model and Set-upmentioning
confidence: 99%
“…Young et al, 2013). REF-B2 is the so-called reference simulation and is a selfconsistent transient simulation from 1960 to 2100 (Eyring et al, 2010). In this simulation the surface time series of halocarbons are based on the adjusted A1 scenario from (Eyring et al, 2010).…”
Section: Site Selection For Temperature Trend Detectionmentioning
confidence: 99%